PENDUGAAN FAKTOR PENENTU PRODUKSI PADI SAWAH SISTEM TANAM LEGOWO DI KELURAHAN DUSUN BESAR KECAMATAN GADING CEMPAKA KOTA BENGKULU - Arianti, Nyayu Neti (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2011)
The aim of this research was to analyze the factors which influence the paddy production of legowo cropping system on Dusun Besar Subdistrict Gading Cempaka District Bengkulu City. The respondents were 56 farmers from 65 farmers of three types of legowo cropping system 4:1, 6:1 dan 8:1 and they were taken with Slovin Formula. The cross section data used in this research include paddy production, land size, seed, urea, labour, and the type of legowo system as dummy variables. To determine influencing factors of production, this research applied Cobb Douglass model. The research results showed that seed used is significat factor but has a negative impact on production, while urea and legowo type of 4:1 have positive and significant effect on production.